Comparison of generator circuit-breaker stresses in test laboratory and real service condition. - Canay, I.M.
The paper shows that there may be substantial discrepancies regarding delayed current zeros and circuit-breaker arc energies when exposing a generator circuit-breaker to a short-circuit in a real system or in a test lab. Depending on the pre-loading of the generator in the real system the degree of asymmetry may be far higher than that being adjustable in a test lab. Based on realistic generator data the courses of the short-circuit currents have been simulated for various cases also taking into account the arc voltages of different circuit-breaker types. For the same breaking current zero crossings may be delayed for several periods and arc energies may be substantially different in the real system compared to the test lab. Improved generator modeling is indispensable for correct simulation of such phenomena and explains more over ?voltage depression?
Keywords: Arc energies; Arc voltages; Breaking current; Circuit-breaker arc energies; Delayed current zeros; Generator circuit-breaker.; Generator circuit-breaker stresses; Generator modeling; Generator pre-loading.; Real service condition; Short-circuit.; Short-circuit currents; Test lab; Test laboratory; Voltage depression